(7-2)-(-3t+1)=-3(1-3t)

Simple and best practice solution for (7-2)-(-3t+1)=-3(1-3t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7-2)-(-3t+1)=-3(1-3t) equation:


Simplifying
(7 + -2) + -1(-3t + 1) = -3(1 + -3t)

Combine like terms: 7 + -2 = 5
(5) + -1(-3t + 1) = -3(1 + -3t)
5 + -1(-3t + 1) = -3(1 + -3t)

Reorder the terms:
5 + -1(1 + -3t) = -3(1 + -3t)
5 + (1 * -1 + -3t * -1) = -3(1 + -3t)
5 + (-1 + 3t) = -3(1 + -3t)

Combine like terms: 5 + -1 = 4
4 + 3t = -3(1 + -3t)
4 + 3t = (1 * -3 + -3t * -3)
4 + 3t = (-3 + 9t)

Solving
4 + 3t = -3 + 9t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-9t' to each side of the equation.
4 + 3t + -9t = -3 + 9t + -9t

Combine like terms: 3t + -9t = -6t
4 + -6t = -3 + 9t + -9t

Combine like terms: 9t + -9t = 0
4 + -6t = -3 + 0
4 + -6t = -3

Add '-4' to each side of the equation.
4 + -4 + -6t = -3 + -4

Combine like terms: 4 + -4 = 0
0 + -6t = -3 + -4
-6t = -3 + -4

Combine like terms: -3 + -4 = -7
-6t = -7

Divide each side by '-6'.
t = 1.166666667

Simplifying
t = 1.166666667

See similar equations:

| 12yards= | | 28=5+6x | | 5/3a-4/3a=1/12 | | -367x=-139 | | (2x-6)+(2x-6)+(x+3)+(x+3)=24 | | 5(x+3)-2=2-1x+9 | | 50=2(15+w) | | x+4x+3x+2x=144 | | -9x+27=-45 | | -12x-(-4)+8x=12x | | 2a-4=3a-5 | | 7n=-2m+10 | | 6x^2+4x-14=0 | | (x+6)+(5x)+(3x+3)=4(x+6) | | 29=x-168 | | 4p-3forx=3 | | 3(-5.4n+1)+5.6n=26.5 | | 2x+5+5x=-12 | | =84 | | 5log-7m+4=-6 | | 25+3x-x=x+4 | | 50=2(15+x) | | M-5=150 | | x^3+12x^2-5x=0 | | .35s+.6(30-s)=.45(30) | | 3y+4=8-(y+6) | | 6x-80=160 | | 34(6-7x)=4x+9 | | 0.65+0.33t=3.63t-0.67 | | 3p^2=6p | | 15z=90 | | 14+-2(3p+1)=6(4+p) |

Equations solver categories